Method for removing calcium, magnesium and sodium from industrial-grade lithium phosphate
Through three-step impurity removal methods, including acid extraction, ion exchange resin adsorption and combined complexing agent treatment, the calcium, magnesium and sodium impurities in lithium phosphate were successfully reduced, and its performance as a positive electrode material for power batteries was improved. Issues of the impact of impurities in existing industrial grade lithium phosphate.
Patent Information
- Application Number
- CN202411261487.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-24
AI Technical Summary
The existing industrial-grade lithium phosphate contains a large amount of calcium, magnesium and sodium impurities, which affects its performance as a positive electrode material for power batteries and cannot meet battery production needs.
Three-step impurity removal method is adopted: firstly extract the calcium, magnesium, sodium ions into the organic phase by saponification of acidic extractor, then use ion exchange resin for adsorption, and finally mix with the combined complexing agent and heat and stir, filter and dry, gradually reduce impurities content to reach battery level purity.
Effectively reduce the content of calcium, magnesium and sodium impurities in lithium phosphate, so that it has the comprehensive application performance of electronic-grade functional materials, and is suitable for lithium source materials of positive electrode materials.
Smart Images

Figure CN119176531A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery raw materials, and in particular to a method for removing calcium, magnesium and sodium from industrial-grade lithium phosphate. Background Art
[0002] With the rapid development of new energy vehicles, the demand for power batteries continues to increase. However, the core factors that affect or restrict the development of power batteries are resources such as nickel, cobalt, and lithium. Among them, lithium resources have a crucial impact on the cost of batteries and vehicles. The lithium source raw materials used in the preparation of traditional positive electrode materials are mainly lithium carbonate and lithium hydroxide monohydrate. Affected by current international and domestic resources and prices, the price will still be as high as about 90,000 yuan / ton in July 2024, which is still more than 1 times the price in 2020. Therefore, the use of lithium compound products with certain cost advantages can continuously reduce costs and enrich available resources. Compared with battery-grade lithium carbonate or lithium hydroxide, the price of lithium phosphate is only 60% of the former, and in the precipitation of lithium phosphate, Li + In the process, Li + The utilization rate is high, and the Li content in the remaining lithium precipitation mother liquor is less than 5%. Therefore, it is quite advantageous to use lithium phosphate to supplement the current lithium carbonate / lithium hydroxide application, and it has certain advantages in being used for electronic grade functional raw materials to modify the performance of positive electrode materials. However, the current Li3PO4 prepared by recycling lithium ore, brine or waste batteries is industrial grade lithium phosphate, which contains a large amount of calcium, magnesium and sodium impurities, which affects the performance of positive electrode materials and cannot meet the production of power batteries. Summary of the invention
[0003] The purpose of the present invention is to provide a method for removing calcium, magnesium and sodium from industrial-grade lithium phosphate, which adopts a three-step impurity removal method to gradually reduce the impurity content in the lithium phosphate after treatment. After the third step of treatment, the impurity content reaches a level that is basically equivalent to the calcium, magnesium and sodium content in battery-grade lithium carbonate or lithium hydroxide monohydrate, so that the lithium phosphate has the comprehensive application performance of electronic-grade functional materials and lithium source raw materials for positive electrode materials.
[0004] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0005] The present invention provides a method for removing calcium, magnesium and sodium from industrial-grade lithium phosphate, comprising the following steps:
[0006] (1) adding ammonia water or alkaline solution to an acidic extractant for saponification to obtain an acidic extractant saponified solution, adding the acidic extractant saponified solution to industrial-grade lithium phosphate, and extracting calcium, magnesium and sodium ions into an organic phase, and obtaining extracted lithium phosphate after solid-liquid separation;
[0007] (2) adding ion exchange resin and water to the lithium phosphate extracted in step (1), mixing and stirring, and obtaining adsorbed lithium phosphate after separation;
[0008] (3) mixing the lithium phosphate adsorbed in step (2) with the combined complexing agent powder, adding dilute hydrochloric acid to adjust the pH, heating and stirring, sieving and separating, and drying to obtain lithium phosphate after impurities are removed.
[0009] The following is a detailed description:
[0010] Step (1) extraction:
[0011] The structure of lithium phosphate:
[0012] The acidic extractant in step (1) is one or more selected from tributyl phosphate (TBP), dioctyl octyl phosphate, di(2-ethylhexyl) hexyl phosphate, trioctylmethylammonium chloride, ethyl acetate, and butyl acetate.
[0013] In some embodiments, the mass ratio of the industrial-grade lithium phosphate to the acidic extractant in step (1) is 1:1-8, preferably 1:2-6, and more preferably 1:3-5.
[0014] In some embodiments, the extraction temperature of step (1) is 20-35° C., and the pH is controlled at 8-10.
[0015] Preferably, step (1) further comprises: regenerating the extractant:
[0016] Add stripping solution to the extracted organic phase, adjust the pH to 6-8, transfer calcium, magnesium and sodium ions into the stripping solution, and return the extracted organic phase to step (1.1) for recycling.
[0017] Preferably, the stripping solution is one of pure water, deionized water, grade II pure water, and ultrapure water, preferably deionized water or grade II pure water.
[0018] Preferably, the volume ratio of the extracted organic phase to the stripping solution is 1.5-3:1, preferably 2-3:1, and more preferably 3:1.
[0019] First, the saponification of the extractant. Acidic extractants usually use saponification technology to improve extraction efficiency and control extraction volume; second, extraction, the extractant and Ca 2+ Mg 2+ and Na + The extractant generated by the reaction has a large solubility in the organic phase, so that the calcium, magnesium and sodium ions are extracted into the organic phase; finally, the extractant is regenerated, and the calcium, magnesium and sodium ions are transferred into the stripping solution through the contact between the stripping solution and the extractant, so that the extractant can be recovered and recycled.
[0020] Step (2) ion exchange resin adsorption:
[0021] The ion exchange resin in step (2) is a weak acid ion exchange resin or a strong acid ion exchange resin, which can stably exchange with divalent metal ions in solution; the ion exchange resin only forms a stable complex with divalent metal ions, and the functional groups on the resin have specific selectivity for certain metal ions. Resins with corresponding functional groups can be selected to remove calcium, magnesium, and sodium ions.
[0022] Preferably, the ion exchange resin model is one or a combination of two or more of 732, CH-93, D401, 401, D113, D403, D408, H103, KPA201B, and the structure is as follows:
[0023]
[0024] In some embodiments, step (2) comprises:
[0025] First, add 732 or D403 type ion exchange resin and water to the lithium phosphate extracted in step (1), mix and stir; then add D113 type ion exchange resin and water, mix and stir, and separate to obtain the adsorbed lithium phosphate.
[0026] Preferably, the mass ratio of the extracted lithium phosphate, the ion exchange resin added each time, and the water added each time is 1:5-10:20-30, preferably 1:5-8:20-25, more preferably 1:5:20;
[0027] Step (3) Complexation:
[0028] The combined complexing agent in step (3) is a combination of EDTA, nitrilotriacetic acid and glycine. Preferably, the mass ratio of EDTA, nitrilotriacetic acid and glycine is 5-8:3-1:2-1, preferably 6:2:2 or 7:1.5:1.5.
[0029] In some embodiments, the mass ratio of the adsorbed lithium phosphate to the combined complexing agent in step (3) is 1:20-10, preferably 1:15, and more preferably 1:10.
[0030] In some embodiments, step (3) adjusts the pH to 5-7, the heating and stirring temperature is 50-80° C., and the time is controlled at 120-210 min.
[0031] In some embodiments, the drying temperature in step (3) is 40-80° C., the vacuum degree is -0.06 to -0.09 MPa, and the drying time is 4-10 h;
[0032] Preferably, the drying temperature in step (3) is 60-70° C., the vacuum degree is -0.08 to -0.09 MPa, and the drying time is 4-6 h.
[0033] The prepared lithium phosphate has calcium, magnesium and sodium contents substantially equivalent to those in lithium carbonate or lithium hydroxide monohydrate; the prepared lithium phosphate has the comprehensive application performance of electronic-grade functional materials and battery-grade lithium source raw materials for positive electrode materials.
[0034] Technical effects:
[0035] The present invention uses a three-step method to gradually reduce impurities in lithium phosphate. The step-by-step impurity removal method can effectively control and reduce the Ca, Mg, and Na metallic impurities in lithium phosphate. The lithium phosphate provided by the present invention has the comprehensive application performance of electronic-grade functional materials and lithium source raw materials for positive electrode materials.
[0036] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a flow chart of the process for removing calcium, magnesium and sodium from industrial-grade lithium phosphate of the present invention;
[0038] Figure 2 Schematic diagram of the extraction process;
[0039] Figure 3 This is the SEM image of lithium phosphate. DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0041] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0042] In the following embodiments of the present invention, the industrial-grade lithium phosphate selected can be purchased from the market as a raw material of the same required specification, or can be prepared according to a conventional synthesis method. For example, lithium phosphate is prepared by reacting industrial-grade phosphoric acid and industrial-grade lithium hydroxide monohydrate, and the reaction equation is 2LiOH·H2O+H3PO4→Li3PO4+3H2O.
[0043] In the following embodiments of the present invention, the selected extractant and complexing agent can be purchased from the same raw materials on the market, or can be prepared according to a known synthesis method. The selected stripping agent adopts a laboratory-made solution, and the selected ion exchange resin models are 732 and D113 or D403 and D113.
[0044] Example 1
[0045] like Figure 1 , 2 The process for removing calcium, magnesium and sodium from industrial-grade lithium phosphate described in this embodiment comprises the following steps:
[0046] (1) Weigh 30 g of lithium phosphate raw material with a Ca content of 3000 ppm, a Mg content of 1000 ppm, and a Na content of 4000 ppm.
[0047] (2) tributyl phosphate was added with ammonia water to adjust the pH to 10.0-11.0 to obtain 300 ml of tributyl phosphate saponified solution with a concentration of 30%, and the above lithium phosphate raw material was added. The pH was adjusted to between 8.0 and 9.0 with 5% NaOH aqueous solution, the temperature was 27±2°C, and the reaction was carried out for 60 minutes before solid-liquid separation.
[0048] (3) Add 1 / 3 of the volume of water to the extracted organic phase, adjust the pH to 6-8 with 0.5 mol / L HCl aqueous solution, and perform back extraction to obtain a recyclable extract. At this time, the Ca, Mg, and Na impurities in the extracted lithium phosphate are 700 ppm, 450 ppm, and 964 ppm, respectively, as determined by ICP.
[0049] (4) Take 10g of lithium phosphate extracted in step (3) and 50g of ion exchange resin D403, add 200g of deionized water and mix, stir at 200r / min for 2h, then add 50g of ion exchange resin D113 and 200g of deionized water and mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 300ppm, 230ppm, and 421ppm respectively according to ICP detection.
[0050] (5) The lithium phosphate treated by resin adsorption in step (4) is then subjected to complexation treatment. 100 g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine powder in a mass ratio of 6:2:2 is mixed with 10 g of lithium phosphate treated in step (4), and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300 r / min, and the mixture is heated in a 60°C water bath for 150 min. After the complexation treatment, the purity of the lithium phosphate and its impurity content can meet the standard requirements of electronic-grade functional materials and positive electrode materials and battery-grade lithium source raw materials. In the experiment, the total yield of lithium phosphate was 93.4%, and the purity of lithium phosphate detected by ICP was 99.61%. The impurities of Ca, Mg and Na were 40 ppm, 61 ppm and 157 ppm respectively. The SEM image of lithium phosphate is as follows Figure 3 As shown, it can be seen that the particle size distribution is relatively uniform, and the nanosheet and nanorod morphologies are relatively clear.
[0051] Example 2
[0052] like Figure 1 , 2 The process for removing calcium, magnesium and sodium from industrial-grade lithium phosphate described in this embodiment comprises the following steps:
[0053] (1) Weigh 100 g of a lithium phosphate raw material having a Ca content of 3000 ppm, a Mg content of 1000 ppm, and a Na content of 4000 ppm.
[0054] (2) tributyl phosphate was added with ammonia water to adjust the pH to 10.0-11.0 to obtain 1000 ml of tributyl phosphate saponified solution with a concentration of 30%, to which the above lithium phosphate raw material was added, and the pH was adjusted to between 8.0-9.0 with 5% NaOH aqueous solution, the temperature was 27±2°C, and the reaction was carried out for 60 minutes before solid-liquid separation.
[0055] (3) Add 1 / 3 of the volume of water to the extracted organic phase, adjust the pH to 6-8 with 0.5 mol / L HCl aqueous solution, and perform back extraction to obtain a recyclable extract. At this time, the Ca, Mg, and Na impurities in the extracted lithium phosphate are 689 ppm, 437 ppm, and 957 ppm, respectively, as determined by ICP.
[0056] (4) Take 50g of lithium phosphate extracted in step (3) and 250g of ion exchange resin D403, add 1000g of deionized water and mix, stir at 200r / min for 3h, then add 250g of ion exchange resin D113 and 1000g of deionized water and mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 308ppm, 216ppm, and 415ppm respectively according to ICP detection.
[0057] (5) The lithium phosphate treated by resin adsorption in step (4) is subjected to complexation treatment. 500g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine in a mass ratio of 6:2:2 is taken, mixed with 50g of lithium phosphate treated in step (4), and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300r / min, and the water bath is heated at 60°C for 150min. After the complexation treatment, the purity of lithium phosphate and the impurity content thereof can meet the standard requirements of electronic grade functional materials and positive electrode materials battery grade lithium source raw materials. In the experiment, the total yield of lithium phosphate was 92.6%, the purity of lithium phosphate was 99.56% after ICP detection, and the impurities of Ca, Mg and Na were 42ppm, 66ppm and 180ppm respectively.
[0058] Example 3
[0059] like Figure 1 , 2The process for removing calcium, magnesium and sodium from industrial-grade lithium phosphate described in this embodiment comprises the following steps:
[0060] (1) Weigh 30 g of lithium phosphate raw material with a Ca content of 3000 ppm, a Mg content of 1000 ppm, and a Na content of 4000 ppm.
[0061] (2) tributyl phosphate was added with ammonia water to adjust the pH to 10.0-11.0 to obtain 300 ml of tributyl phosphate saponified solution with a concentration of 30%, and the above lithium phosphate raw material was added. The pH was adjusted to between 8.0 and 9.0 with 5% NaOH aqueous solution, the temperature was 27±2°C, and the reaction was carried out for 60 minutes before solid-liquid separation.
[0062] (3) Add 1 / 3 of the volume of water to the extracted organic phase, adjust the pH to 6-8 with 0.5 mol / L HCl aqueous solution, and perform back extraction to obtain a recyclable extract. At this time, the Ca, Mg, and Na impurities in the extracted lithium phosphate are 700 ppm, 450 ppm, and 962 ppm, respectively, as determined by ICP.
[0063] (4) Take 10g of lithium phosphate extracted in step (3) and 50g of ion exchange resin 732, add 200g of deionized water and mix, stir at 200r / min for 2h, then add 50g of ion exchange resin D113 and 200g of deionized water and mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 300ppm, 230ppm, and 458ppm respectively according to ICP detection.
[0064] (5) The lithium phosphate treated by resin adsorption in step (4) is subjected to complexation treatment. 100 g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine in a mass ratio of 6:2:2 is mixed with 10 g of lithium phosphate treated in step (4), and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300 r / min, and the mixture is heated in a water bath at 60°C for 150 min. After the complexation treatment, the purity of the lithium phosphate and the impurity content thereof can meet the standard requirements of electronic-grade functional materials and positive electrode materials for battery-grade lithium source raw materials. In the experiment, the total yield of lithium phosphate was 93.6%, the purity of lithium phosphate was 99.60% as determined by ICP, and the impurities of Ca, Mg and Na were 38 ppm, 59 ppm and 164 ppm respectively.
[0065] Example 4
[0066] like Figure 1 , 2 The process for removing calcium and magnesium from industrial-grade lithium phosphate described in this embodiment includes the following steps:
[0067] (1) Weigh 100 g of a lithium phosphate raw material having a Ca content of 3000 ppm, a Mg content of 1000 ppm, and a Na content of 4000 ppm.
[0068] (2) tributyl phosphate was added with ammonia water to adjust the pH to 10.0-11.0 to obtain 1000 ml of tributyl phosphate saponified solution with a concentration of 30%, to which the above lithium phosphate raw material was added, and the pH was adjusted to between 8.0-9.0 with 5% NaOH aqueous solution, the temperature was 27±2°C, and the reaction was carried out for 60 minutes before solid-liquid separation.
[0069] (3) Add 1 / 3 of the volume of water to the extracted organic phase, adjust the pH to 6-8 with 0.5 mol / L HCl aqueous solution, and perform back extraction to obtain a recyclable extract. At this time, the Ca, Mg, and Na impurities in the extracted lithium phosphate are 689 ppm, 437 ppm, and 956 ppm, respectively, as determined by ICP.
[0070] (4) Take 50g of lithium phosphate extracted in step (3) and 250g of ion exchange resin 732, add 1000g of deionized water and mix, stir at 200r / min for 3h, then add 250g of ion exchange resin D113 and 1000g of deionized water and mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 308ppm, 216ppm, and 426ppm respectively according to ICP detection.
[0071] (5) The lithium phosphate treated by resin adsorption in step (4) is subjected to complexation treatment. 500g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine in a mass ratio of 6:2:2 is taken, mixed with 50g of lithium phosphate treated in step (4), and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300r / min, and the water bath is heated at 60°C for 150min. After the complexation treatment, the purity of lithium phosphate and the impurity content thereof can meet the standard requirements of electronic grade functional materials and positive electrode materials battery grade lithium source raw materials. In the experiment, the total yield of lithium phosphate was 92.9%, the purity of lithium phosphate was 99.58% after ICP detection, and the impurities of Ca, Mg and Na were 41ppm, 68ppm and 176ppm respectively.
[0072] Comparative Example 1
[0073] The difference from Example 1 is that no ion exchange resin adsorption and combined complexing agent impurity removal are used, and the following steps are included:
[0074] The same as steps (1), (2) and (3) of Example 1. After extraction, the lithium phosphate was tested by ICP and its Ca, Mg and Na impurities were 702 ppm, 446 ppm and 1006 ppm respectively. The purity of the lithium phosphate was 99.15% by ICP.
[0075] Comparative Example 2
[0076] The difference from Example 1 is that no combined complexing agent is used for impurity removal, and the method comprises the following steps:
[0077] The same as steps (1), (2), (3) and (4) of Example 1. The lithium phosphate adsorbed by the ion exchange resin after screening was tested by ICP. The Ca, Mg and Na impurities were 306 ppm, 233 ppm and 438 ppm respectively. The purity of the lithium phosphate tested by ICP was 99.32%.
[0078] Comparative Example 3
[0079] The difference from Example 1 is that no extraction and combined complexing agent are used for impurity removal, and only ion exchange resin is used for impurity removal, which includes the following steps:
[0080] Weigh 10g of lithium phosphate raw material with a Ca content of 3000ppm, a Mg content of 1000ppm, and a Na content of 4000ppm, and 50g of ion exchange resin D403, add 200g of deionized water to mix, stir at 200r / min for 2h, then add 50g of ion exchange resin D113 and 200g of deionized water to mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. The Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 2554ppm, 816ppm, and 3678ppm respectively. The purity of lithium phosphate detected by ICP is 99.09%.
[0081] Comparative Example 4
[0082] The difference from Example 1 is that no extraction and ion exchange resin are used for impurity removal, and only a combined complexing agent is used for impurity removal, which includes the following steps:
[0083] 100g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine in a mass ratio of 6:2:2 is mixed with 10g of a lithium phosphate raw material having a Ca content of 3000ppm, a Mg content of 1000ppm and a Na content of 4000ppm, and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300r / min, and the mixture is heated in a water bath at 60°C for 150min. The Ca, Mg and Na impurities in the lithium phosphate after complexation are 2489ppm, 786ppm and 3482ppm respectively. The purity of the lithium phosphate is 99.10% as detected by ICP.
[0084] Comparative Example 5
[0085] The difference from Example 1 is that the ion exchange resin D403 is replaced by HP8 chelating adsorption resin, and no combined complexing agent is used for impurity removal, and the method comprises the following steps:
[0086] Same as steps (1), (2) and (3) in Example 1.
[0087] (4) Take 10g of lithium phosphate extracted in step (3) and 50g of ion exchange resin HP8, add 200g of deionized water and mix, stir at 200r / min for 2h, then add 50g of ion exchange resin D113 and 200g of deionized water and mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 1200ppm, 640ppm, and 1411ppm respectively according to ICP detection. The purity of lithium phosphate according to ICP detection is 99.15%.
[0088] Comparative Example 6
[0089] The difference from Example 1 is that the ion exchange resin D403 is replaced by HP8 type chelating adsorption resin, comprising the following steps:
[0090] Same as steps (1), (2) and (3) in Example 1.
[0091] (4) Take 10g of lithium phosphate extracted in step (3) and 50g of ion exchange resin HP8, add 200g of deionized water, stir at 200r / min for 2h, then add 50g of ion exchange resin D113 and 200g of deionized water, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 1200ppm, 640ppm, and 1421ppm respectively according to ICP detection.
[0092] (5) The lithium phosphate treated by resin adsorption in step (4) is subjected to complexation treatment. 100 g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine powder in a mass ratio of 6:2:2 is mixed with 10 g of lithium phosphate treated in step (4), and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300 r / min, and the mixture is heated in a water bath at 60°C for 150 min. The Ca, Mg and Na impurities in the lithium phosphate after complexation treatment are 523 ppm, 418 ppm and 846 ppm respectively. The purity of the lithium phosphate detected by ICP is 99.18%.
[0093] Comparative Example 7
[0094] The difference from Example 1 is that no extraction and combined complexing agent are used for impurity removal, and only the ion exchange resin is replaced with HP8 for impurity removal, which includes the following steps:
[0095] Weigh 10g of lithium phosphate raw material with a Ca content of 3000ppm, a Mg content of 1000ppm, and a Na content of 4000ppm, and 50g of ion exchange resin HP8, add 200g of deionized water to mix, stir at 200r / min for 2h, then add 50g of ion exchange resin D113 and 200g of deionized water to mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. The Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 2648ppm, 852ppm, and 3715ppm respectively, and the purity of the lithium phosphate is 99.07% as detected by ICP.
[0096] Comparative Example 8
[0097] The difference from Example 1 is that the ion exchange resin D113 is not used, and the following steps are included:
[0098] Same as steps (1), (2) and (3) in Example 1.
[0099] (4) Take 10 g of the lithium phosphate extracted in step (3) and 50 g of ion exchange resin DD403, add 200 g of deionized water and mix, stir at 200 r / min for 2 h, and then separate the resin and lithium phosphate with a sieve.
[0100] (5) The lithium phosphate treated by resin adsorption in step (4) is subjected to complexation treatment. 100 g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine powder in a mass ratio of 6:2:2 is mixed with 10 g of lithium phosphate treated in step (4), and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300 r / min, and the mixture is heated in a water bath at 60°C for 150 min. After the complexation treatment, the Ca, Mg and Na impurities are 339 ppm, 262 ppm and 668 ppm respectively by ICP detection. The purity of lithium phosphate detected by ICP is 99.28%.
[0101] Comparative Example 9
[0102] The difference from Example 1 is that no ion exchange resin D113 is used and no combined complexing agent is used for impurity removal, and the method comprises the following steps:
[0103] Same as steps (1), (2) and (3) in Example 1.
[0104] (4) Take 10g of lithium phosphate extracted in step (3) and 50g of ion exchange resin D403, add 200g of deionized water and mix, stir at 200r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 526ppm, 468ppm, and 1372ppm respectively according to ICP detection. The purity of lithium phosphate according to ICP detection is 99.18%.
[0105] Comparative Example 10
[0106] The difference from Example 1 is that the ion exchange resin D403 is not used, and the following steps are included:
[0107] Same as steps (1), (2) and (3) in Example 1.
[0108] (4) Take 10 g of lithium phosphate extracted in step (3) and 50 g of ion exchange resin D113, add 200 g of deionized water and mix, stir at 300 r / min for 2 h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 552 ppm, 468 ppm, and 1491 ppm, respectively, according to ICP detection.
[0109] (5) The lithium phosphate treated by resin adsorption in step (4) is subjected to complexation treatment. 100 g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine powder in a mass ratio of 6:2:2 is mixed with 10 g of lithium phosphate treated in step (4), and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300 r / min, and the mixture is heated in a water bath at 60°C for 150 min. After the complexation treatment, the purity of the lithium phosphate is 99.61% as determined by ICP, and the impurities of Ca, Mg and Na are 318 ppm, 226 ppm and 646 ppm respectively. The purity of the lithium phosphate is 99.34% as determined by ICP.
[0110] Comparative Example 11
[0111] The difference from Example 1 is that the ion exchange resin D403 is not used, and the combined complexing agent is not used for impurity removal, and the following steps are included:
[0112] Same as steps (1), (2) and (3) in Example 1.
[0113] (4) Take 10g of lithium phosphate extracted in step (3) and 50g of ion exchange resin D113, add 200g of deionized water and mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 531ppm, 472ppm, and 1542ppm respectively according to ICP detection. The purity of lithium phosphate according to ICP detection is 99.16%.
[0114] Comparative Example 12
[0115] The difference from Example 1 is that the ion exchange resin D113 is replaced by HP8 type chelating adsorption resin, comprising the following steps:
[0116] Same as steps (1), (2) and (3) in Example 1.
[0117] (4) Take 10g of lithium phosphate extracted in step (3) and 50g of ion exchange resin D403, add 200g of deionized water and mix, stir at 200r / min for 2h, then add 50g of ion exchange resin HP8 and 200g of deionized water and mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 1261ppm, 635ppm, and 1404ppm respectively according to ICP detection.
[0118] (5) The lithium phosphate treated by resin adsorption in step (4) is subjected to complexation treatment. 100 g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine powder in a mass ratio of 6:2:2 is mixed with 10 g of lithium phosphate treated in step (4), and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300 r / min, and the mixture is heated in a water bath at 60°C for 150 min. The Ca, Mg and Na impurities in the lithium phosphate after complexation treatment are 496 ppm, 421 ppm and 811 ppm respectively. The purity of the lithium phosphate detected by ICP is 99.32%.
[0119] Comparative Example 13
[0120] The difference from Example 1 is that the mixed complexing agent is replaced by disodium ethylenediaminetetraacetate for complexing and impurity removal, which includes the following steps:
[0121] Same as steps (1), (2), (3), and (4) of Example 1. Take 100g of disodium ethylenediaminetetraacetic acid complexing agent and mix with 10g of lithium phosphate treated in step (4), then add dilute hydrochloric acid solution to adjust the pH to 6-7, stir with magnetic force at a speed of 300r / min, and heat in a water bath at 60°C for 150min. After the complexing treatment, the Ca, Mg, and Na impurities in the lithium phosphate are 132ppm, 191ppm, and 463ppm, respectively. The purity of the lithium phosphate is 99.29% as determined by ICP. The purity of the lithium phosphate is 99.36% as determined by ICP.
[0122] Comparative Example 14
[0123] The difference from Example 1 is that the mixed complexing agent is replaced by sodium hexametaphosphate for complexing and impurity removal, which includes the following steps:
[0124] Same as steps (1), (2), (3) and (4) of Example 1. Take 100g of sodium hexametaphosphate complexing agent and 10g of lithium phosphate treated in step (4) and mix them. Then add dilute hydrochloric acid solution to adjust the pH to 6-7. The magnetic stirring speed is 300r / min and the mixture is heated in a water bath at 60°C for 150min. After the complexing treatment, the impurities of Ca, Mg and Na in the lithium phosphate are 94ppm, 142ppm and 368ppm respectively. The purity of the lithium phosphate is 99.39% as determined by ICP.
[0125] Comparative Example 15
[0126] The difference from Example 1 is that extraction and ion exchange resin are not used for impurity removal, and the complexing agent is replaced with sodium hexametaphosphate for impurity removal, which includes the following steps:
[0127] Take 100g of sodium hexametaphosphate complexing agent and 10g of lithium phosphate raw material with Ca content reaching 3000ppm, Mg content reaching 1000ppm, and Na content reaching 4000ppm, and then add dilute hydrochloric acid solution to adjust pH 6-7, magnetic stirring speed is 300r / min, and heating in a 60℃ water bath for 150min. After the complexing treatment, the Ca, Mg, and Na impurities in the lithium phosphate are 2594ppm, 812ppm, and 3558ppm respectively. The purity of the lithium phosphate is 99.08% after ICP detection.
[0128] Experimental example
[0129] Physical and chemical indicators
[0130]
[0131] It can be seen that the lithium phosphate prepared based on the calcium, magnesium and sodium removal process method and process system can basically meet the battery-grade lithium phosphate indicators.
[0132] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for removing calcium, magnesium and sodium from industrial-grade lithium phosphate, characterized in that: The following steps are involved: (1) adding ammonia water or alkaline solution to an acidic extractant for saponification to obtain an acidic extractant saponified solution, adding the acidic extractant saponified solution to industrial-grade lithium phosphate, and extracting calcium, magnesium and sodium ions into an organic phase, and obtaining extracted lithium phosphate after solid-liquid separation; (2) adding ion exchange resin and water to the lithium phosphate extracted in step (1), mixing and stirring, and obtaining adsorbed lithium phosphate after separation; (3) mixing the lithium phosphate adsorbed in step (2) with the combined complexing agent, adding dilute hydrochloric acid to adjust the pH, heating and stirring, sieving and separating, and drying to obtain lithium phosphate after impurities are removed.
2. The method according to claim 1, characterized in that The acidic extractant in step (1) is one or more selected from tributyl phosphate (TBP), dioctyl octyl phosphate, di(2-ethylhexyl) hexyl phosphate, trioctylmethylammonium chloride, ethyl acetate, and butyl acetate.
3. The method according to claim 1, characterized in that The mass ratio of the industrial-grade lithium phosphate to the acidic extractant in step (1) is 1:1-8, preferably 1:2-6, and more preferably 1:3-5; The extraction temperature of step (1) is 20-35° C., and the pH is controlled at 8-10.
4. The method according to claim 1, characterized in that: Step (1) also includes: extractant regeneration: Add stripping solution to the extracted organic phase, adjust the pH to 6-8, transfer calcium, magnesium and sodium ions into the stripping solution, and return the extracted organic phase to step (1.1) for recycling; Preferably, the stripping solution is one of pure water, deionized water, grade II pure water, and ultrapure water, preferably deionized water or grade II pure water; Preferably, the volume ratio of the extracted organic phase to the stripping solution is 1.5-3:1, preferably 2-3:1, and more preferably 3:
1.
5. The method according to claim 1, characterized in that The ion exchange resin in step (2) is a weak acid ion exchange resin or a strong acid ion exchange resin; Preferably, the ion exchange resin model is one or more of 732, CH-93, D401, 401, D113, D403, D408, H103, and KPA201B, preferably a combination of 732 and D113, or a combination of D403 and D113; Preferably, step (2) comprises: First, add 732 or D403 type ion exchange resin and water to the lithium phosphate extracted in step (1), mix and stir; then add D113 type ion exchange resin and water, mix and stir, and separate to obtain the adsorbed lithium phosphate.
6. The method according to claim 5, characterized in that The mass ratio of the extracted lithium phosphate, the ion exchange resin added each time and the water added each time is 1:5-10:20-30, preferably 1:5-8:20-25, and more preferably 1:5:
20.
7. The method according to claim 1, characterized in that The combined complexing agent in step (3) is a mixed powder of EDTA, nitrilotriacetic acid and glycine. Preferably, the mass ratio of EDTA, nitrilotriacetic acid and glycine is 5-8:3-1:2-1, preferably 6:2:2 or 7:1.5:1.
5.
8. The method according to claim 1, characterized in that The mass ratio of the adsorbed lithium phosphate to the combined complexing agent in step (3) is 1:20-10, preferably 1:15, and more preferably 1:
10.
9. The method according to claim 1, characterized in that: The mixing and heating temperature of step (3) is 50-80° C., the time is controlled at 120-210 min, and the pH is controlled at 5-7.
10. The method according to claim 1, characterized in that The drying temperature of step (3) is 40-80° C., the vacuum degree is -0.06 to -0.09 MPa, and the drying time is 4-10 h; Preferably, the drying temperature in step (3) is 60-70° C., the vacuum degree is -0.08 to -0.09 MPa, and the drying time is 4-6 h.
Citation Information
Cited By
A method for recycling lithium carbonate lithium precipitation mother liquor
CN122725214A
